2007
DOI: 10.1179/174328507x163896
|View full text |Cite
|
Sign up to set email alerts
|

Interactions among magnetite oxidation, calcination of carbonate minerals and melt formation in iron ore pellets

Abstract: During induration of iron ore pellets produced from magnetite concentrates, there are many reactions occurring simultaneously. While the magnetite is being oxidised to haematite, carbonate fluxes are being calcined, leading to the formation of complex oxides. Calcination of fluxes and the formation of calcium and magnesium ferrites and silicates during the preheat stage can influence the magnetite oxidation process. As the calcination reaction proceeds quicker than oxidation at temperatures experienced during … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 2 publications
0
3
0
Order By: Relevance
“…At temperatures above 1150 °C, the eutectic slag becomes widespread between the magnetite grains, allowing significant sintering to occur (Figure 5). This is different to the outer hematite zone of the pellet where significant molten slag formation does not occur until around 1200 °C (10) . Note that Figure 5 exaggerates the amount of slag formed due to the longer time at temperature and higher gangue composition compared to real iron ore pellets.…”
Section: Results For Compacts With Reduced Oxygenmentioning
confidence: 67%
See 1 more Smart Citation
“…At temperatures above 1150 °C, the eutectic slag becomes widespread between the magnetite grains, allowing significant sintering to occur (Figure 5). This is different to the outer hematite zone of the pellet where significant molten slag formation does not occur until around 1200 °C (10) . Note that Figure 5 exaggerates the amount of slag formed due to the longer time at temperature and higher gangue composition compared to real iron ore pellets.…”
Section: Results For Compacts With Reduced Oxygenmentioning
confidence: 67%
“…Rapid quenching of the samples was performed using a high flowrate of nitrogen gas. The test method used here was originally developed by Firth (10) for the evaluation of firing profiles for pellets produced from Australian magnetite concentrates. Single green balls of a suitable size, about 12.5 mm in diameter, were placed in a nickel foil crucible before being place in the furnace with an R type thermocouple (platinum -platinum-10% rhodium) used to measure the surface temperature of the pellet.…”
Section: Methodsmentioning
confidence: 99%
“…Currently, many metallurgists have carried out a lot of research on the preparation of fluxed pellets [5]. Firth et al [6][7][8] used low-silica magnetite (65.7% Fe (total), 2.3% SiO 2 ) with limestone and dolomite to prepare fluxed pellets with basicity (CaO/SiO 2 ) of 1.0; They found that while the magnetite is being oxidized to haematite, carbonate fluxes are being calcined, leading to the formation of complex oxides. Calcination of fluxes and the formation of calcium and magnesium ferrites and silicates during the preheat stage can influence the magnetite oxidation process.…”
Section: Introductionmentioning
confidence: 99%